Anomalies detection in adhesive wall tiling systems by infrared thermography - Lourenço, T. (2017)
Submitted by Luís Matias (lmatias@lnec.pt) on 2017-06-21T14:26:28Z No. of bitstreams: 1 RI - Lourenco et al_IRT tiling systems__JCBM 2017_prof.pdf: 4017717 bytes, checksum: c60bbdcdc90fe6c487fe99e822cece73 (MD5)